HUBUNGAN TINGKAT KECEMASAN DENGAN KUALITAS TIDUR PASIEN DI RUANG RAWAT INAP RUMAH SAKIT UMUM DAERAH MOKOYURLI KABUPATEN BUOL - Ni Ketut Elmiyanti; Jumain (Pustaka Katulistiwa : Karya Tulis Ilmiah Keperawatan, 2022)
A person can sleep or not be influenced by several factors, one of which is feelings of anxiety. Anxiety is an individual's response to an unpleasant situation, which describes a state of worry, erratic anxiety. Based on the results of observations and interviews, the results obtained from 4 patients who were treated, 3 of them experienced anxiety and sleep disorders. The purpose of this study was to find out "The Correlation of Anxiety Levels with Patient Sleep Quality in the Inpatient Room of Mokoyurli Hospital, Buol Regency". The research design was analytic design with cross sectional type. The total population is all patients encountered during the study with a sample of 41 respondents. Sampling in this study is by using the proportion estimation formula, the sampling technique used in this study is non-probability sampling by means of Accidental Sampling. The results of the univariate study showed that poor sleep quality was greater in the number of 28 people (68.3%) compared to those who experienced good sleep quality, which was less, amounting to 13 people (31.7%). Moderate anxiety was 23 people (56.1%), while mild anxiety was 18 people (43.9%). Bivariate analysis with Chi Square statistical test with a significant level of (0.05). The results of statistical tests obtained p value = 0.010 which means that p <α (0.05) there is a relationship between anxiety levels and sleep quality of patients in the inpatient ward of the Mokoyurli General Hospital, Buol Regency. The conclusion in this study is that there is a relationship between the level of anxiety and the quality of sleep of patients in the Inpatient Room of the Mokoyurli Regional General Hospital, Buol Regency. It is recommended that the inpatient room environment be further improved in terms of patient comfort